Experimental Study of the Effectiveness of Sacrificial Cladding Using Polymeric Foams as Crushable Core with a Simply Supported Steel Beam. (4th September 2016) - Ousji, H.; Belkassem, B.; Louar, M. A.; Reymen, B.; Pyl, L.; Vantomme, J.
Abstract : The present paper focuses on the study of the effectiveness of the sacrificial cladding using polymeric foam as crushable core to reduce the delivered blast energy using a simplified structure. The latter consists of a simply supported steel beam under a localized blast load. The tested sacrificial cladding has a cross-sectional area of 80 × 80 mm 2 . The effect of the front plate mass and the crushable core properties (plateau stress and thickness) is studied. Three polymeric foams are investigated: (a) the expanded polystyrene foam (PS13) with a density of 13 kg/m 3, (b) the closed-cell polyurethane (PU30) with a density of 30 kg/m 3, and (c) the open-cell polyurethane (PU50) with a density of 50 kg/m 3 . Four front plate masses are used: 144, 188, 336, and 495 g. All possible combinations are tested to determine their absorption capacity. The obtained results show that the absorption capability increases by increasing the front plate mass, the plateau stress, and the thickness of the crushable core. The open-cell polyurethane PU50 performs better. Disintegration problems are observed on the expanded polystyrene PS13 after the end of the compression process.